Frequency of benzodiazepine use in elderly primary care patients - Kovačević, Milena; Jovanović, Marija; Ćulafić, Milica; Roganović, Maša; Vučićević, Katarina; Vezmar Kovačević, Sandra; Miljković, Branislava (Archives of Pharmacy, 2022)
The use of benzodiazepines in elderly patients is associated with the numerous adverse outcomes, such as an increased risk of falls, fractures, health care costs, and even mortality. The aim was to investigate the frequency of benzodiazepine use in patients aged ≥65 years, and to explore the association of their use with patient characteristics. Demographic, clinical, and therapy characteristics were collected prospectively in the community pharmacies. Data analysis was performed using SPSS software (ver. 25). The study included 287 patients, with a mean age of 72.2±5.8 years (total range 65-91), the average number of drugs 7.6±2.2 (4-18), and the average number of indications 4.5±1.7 (1-11). The total prevalence of benzodiazepine use was 28.9%, long-acting 24.0% and short-acting 5.2%. The most commonly used was bromazepam (17.1%), followed by diazepam (7.0%), lorazepam (3.8%) and alprazolam (1.4%). In the patients aged 65-69 years, the prevalence of benzodiazepine use was 29.3%, 70-74 years 33.7%, 75-80 years 23.3% and in ≥80 years 24.0%. The use of benzodiazepines was statistically significantly more common in patients diagnosed with anxiety, other mental illness, but also with the comedication with bisphosphonates, analgesics or herbal medicine Ginkgo biloba leaf extract (p<0.05). A high frequency of benzodiazepine use was determined in elderly patients. Community pharmacists can play a significant role in assessing and minimizing the risk of adverse events. Interventions may include counseling on the prevention of falls, but also the possibility of drug discontinuation when there is no convincing indication for their long-term use.